Gaseous nitrogen and carbon emissions from a full-scale deammonification plant - Weissenbacher, Norbert (Water environment research : a research publication of the Water Environment Federation, 2010)
The aim of this work was to give a quantitative description of the gaseous nitrogen and carbon emissions of a full-scale deammonification plant (DEMON system). Deammonification accounted for the net carbon sequestration of 0.16 g CO2/g NO2-N. Both nitrogen dioxide (NO2) and nitric oxide (NO) were minor trace gases (<0.1% nitrogen output). However, in comparison, the nitrous oxide (N2O) emission (1.3% nitrogen output) was significant. The global warming potential of the N2O emissions from the DEMON were similar to those found in conventional simultaneous nitrification/denitrification systems; however, CO2 emissions in the investigated system were significantly lower, thereby lessening the overall environmental effect. This was the first time such an analysis has been performed on a DEMON system